2010
DOI: 10.1017/s1751731110001059
|View full text |Cite
|
Sign up to set email alerts
|

An individual-based model simulating goat response variability and long-term herd performance

Abstract: Finding ways of increasing the efficiency of production systems is a key issue of sustainability. System efficiency is based on long-term individual efficiency, which is highly variable and management driven. To study the effects of management on herd and individual efficiency, we developed the model simulation of goat herd management (SIGHMA). This dynamic model is individual-based and represents the interactions between technical operations (relative to replacement, reproduction and feeding) and individual b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
9
0
4
Order By: Relevance
“…The 'portfolio effect' states that communities with higher species richness are more likely to include the species that is best adapted to any given condition in fluctuating environments so that the number of species per se has a positive effect on system resilience (Dumont et al, 2017). Within herds, diversity of individual trade-offs between functions that was quantified in dairy goats (Puillet et al, 2010) and dairy cows (Ollion et al, 2016) does not increase herd milk production but is assumed to stabilise it under fluctuating environmental conditions. Abiotic and biotic interactions, including biogeochemical cycles and trophic interactions, lend ruminant systems further resilience properties (Dumont et al, 2017).…”
Section: Historical Perspectivementioning
confidence: 99%
“…The 'portfolio effect' states that communities with higher species richness are more likely to include the species that is best adapted to any given condition in fluctuating environments so that the number of species per se has a positive effect on system resilience (Dumont et al, 2017). Within herds, diversity of individual trade-offs between functions that was quantified in dairy goats (Puillet et al, 2010) and dairy cows (Ollion et al, 2016) does not increase herd milk production but is assumed to stabilise it under fluctuating environmental conditions. Abiotic and biotic interactions, including biogeochemical cycles and trophic interactions, lend ruminant systems further resilience properties (Dumont et al, 2017).…”
Section: Historical Perspectivementioning
confidence: 99%
“…Characterizing the three groups of MDH farmers' management strategies revealed that herd performances emerge from complex interactions between biological resources (particularly breed composition) and the decisional component (Puillet et al, 2010). Farmers in Group 1 seek a combination of animals or an animal (through cross-breeding) that provides a win-win situation between milk yields and low concentrate dependency.…”
Section: Multi-breed Herd Performances and Managementmentioning
confidence: 99%
“…Modelling studies accounting for a diversity of female functional profiles have provided some conceptual evidence that individual variability may help to maintain the production and ecological efficiency of ruminant farms (Tichit et al, 2011;Blanc et al, 2013). The diversity of individual tradeoffs between functions has been quantified in herds of dairy cows (Ollion et al, 2016), suckler cows (de la Torre et al, 2015) and dairy goats (Puillet et al, 2010). Such a diversity of trade-off profiles does not increase herd milk production but enables performance stability under fluctuating environmental conditions (Blanc et al, 2013), leading to more consistent economic margins for farmers.…”
Section: Use Of Cross-bred Animalsmentioning
confidence: 99%